2007
DOI: 10.4049/jimmunol.179.1.532
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic and Therapeutic Use of Antibodies for Protection against Respiratory Infection with Francisella tularensis

Abstract: The role of Abs in protection against respiratory infection with the intracellular bacterium Francisella tularensis is not clear. To investigate the ability of Abs to clear bacteria from the lungs and prevent systemic spread, immune serum was passively administered i.p. to naive mice before intranasal F. tularensis live vaccine strain infection. It was found that immune serum treatment provided 100% protection against lethal challenge while normal serum or Ig-depleted immune serum provided no protection. Prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
143
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(158 citation statements)
references
References 31 publications
13
143
1
1
Order By: Relevance
“…Temastan iki gün içinde imm ün serum verildiğin-de koruyucudur. Tularemi etkenine maruz kalan farelere normal serum veya immünoglobulin içermeyen serumlar verildiğinde koruyucu olmadığı görülmüştür (56). Bu veriler immün serumun hem tedavi hem de temas sonrası profilaktik uygulama için olası rolünü göstermekle birlikte, bu sonuçların diğer tularemi infeksiyon modellerinde de desteklenmesi gereklidir.…”
Section: Pasif İmmünizasyonunclassified
“…Temastan iki gün içinde imm ün serum verildiğin-de koruyucudur. Tularemi etkenine maruz kalan farelere normal serum veya immünoglobulin içermeyen serumlar verildiğinde koruyucu olmadığı görülmüştür (56). Bu veriler immün serumun hem tedavi hem de temas sonrası profilaktik uygulama için olası rolünü göstermekle birlikte, bu sonuçların diğer tularemi infeksiyon modellerinde de desteklenmesi gereklidir.…”
Section: Pasif İmmünizasyonunclassified
“…Transfer of peritoneal leukocytes and serum from immune mice into naïve mice resulted in survival of 10% of the mice when challenged with fully virulent F. tularensis SchuS4; rechallenged 6 weeks later, all the surviving mice died (1). However, more than 40 years later, there have been only a few studies that investigated the ability of passively transferred antibodies to protect against infection, with results demonstrating that immune serum may be protective in the presence of a coordinated host response (21,30,52,53).…”
mentioning
confidence: 99%
“…As mentioned previously, transfer of serum from mice immunized against F. tularensis protected mice challenged in a LVS respiratory infection model [35]. Normal sera or immunoglobulin-deplete sera were not protective.…”
Section: Antibodies/passive Immune Serummentioning
confidence: 98%
“…Other reviews have suggested that passive immune transfer may be useful in certain circumstances [34]. A recent study in mice demonstrated the passive immunization of immune serum-protected mice in a LVS infection model [35]. Further study on the role of antibodies in protection against tularemia infection is important for both vaccine development and possible therapeutic products.…”
mentioning
confidence: 99%